2001
DOI: 10.1080/01140671.2001.9514170
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium concentrations in some New Zealand wheat grain

Abstract: simple correlations between major soil properties and wheat grain Cd concentrations for either winter or spring wheat. For winter wheat, a multiple regression model with terms for total zinc (Zn) and CaCl 2 -extractable Cd yielded the highest correlation with winter wheat Cd concentrations (r 2 = 0.59 P < 0.05). Low Cd accumulating wheat cultivars can be selected for use at sites where the Cd concentration in grain exceeds the MPC. Future work is required to determine which soil properties are important in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 34 publications
2
12
3
Order By: Relevance
“…The element composition of the wheat grain (or wheat flour in the case of As) is also summarised using previously published data (Isikl et al, 1998;Gonzáles et al, 2001;Gray et al, 2001;Souci et al, 2000;Zhao et al, 2004;Tremel et al, 1997). For most elements the concentrations found in the grain correspond well with the earlier reported values.…”
Section: Resultssupporting
confidence: 75%
“…The element composition of the wheat grain (or wheat flour in the case of As) is also summarised using previously published data (Isikl et al, 1998;Gonzáles et al, 2001;Gray et al, 2001;Souci et al, 2000;Zhao et al, 2004;Tremel et al, 1997). For most elements the concentrations found in the grain correspond well with the earlier reported values.…”
Section: Resultssupporting
confidence: 75%
“…Wheat grain Cd concentration measured in this study did not exceed the proposed tolerance level for Cd in wheat grain of 235 mg kg (1 DM (EC 2001;FAO/WHO 2001). The mean value of wheat grain Cd concentration in this study with hard red spring wheat was close to those observed in New Zealand, France, Sweden, and the United Kingdom, ranging from 53 to 77 mg kg (1 DM (Mench 1998;Gray et al 2001;Wa˚ngstrand 2005 ; Table 3), and 24Á64% lower than those reported for durum wheat in the United States and western Canada Norvell et al 2000; Table 3). Cadmium accumulation in plants differs with species and among cultivars within species .…”
Section: Cadmium Concentration In Wheat Grainsupporting
confidence: 82%
“…Many crop species, including wheat (Tritium aestivum L.), have been reported to accumulate Cd to an extent that may exceed the proposed maximum level for human consumption without adverse effects on crop growth (Chaudri et al 1995;Gawalko et al 2001;Gray et al 2001). A maximum permissible concentration (MPC) of Cd in wheat grain has been established by national and international health authorities in response to the potential health risks of Cd accumulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same Cd loading rate, Cd concentrations in leaves of radish were significantly (P < 0.001) ( Table 5) higher than those in roots by factors of 2.62 to 3.95 in the Calcaric Cambisols and 1.61 to 4.10 in the Ferralsols. This different pattern in concentration and distribution of Cd in different plant tissues depends on the plant species (Choudhary et al, 1994;Yang et al, 1995;Gray et al, 2001) and may be related in part to Cd tolerance (Dowdy and Larson, 1975;Cumming and Tomsett, 1992;McKenna et al, 1993;He and Singh, 1994;Jiang et al, 2002;Ru et al, 2004). Accumulation of high levels of Cd in the non-edible parts may limit the accumulation of Cd in edible portions of the plant (Grant et al, 1998).…”
Section: Cadmium Concentrations In Plant Tissuesmentioning
confidence: 99%